PENGARUH PROFITABILITAS DAN KEPUTUSAN INVESTASI SERTA KEPUTUSAN PENDANAAN TERHADAP NILAI PERUSAHAAN SEKTOR PERTAMBANGAN DI INDONESIA - Ni Putu Taris Aprilia Dewi; Ni Luh Anik Puspa Ningsih; Made Pratiwi Dewi (Warmadewa Management and Business Journal (WMBJ), 2025)
The high potential of the mining sector has led to an increase in investment. Investors consider the value of a company before investing their capital, which is reflected in the PBV value. Fluctuations in PBV values result in differences in the value of each mining company. An increase in PBV values indicates that a company has successfully realized its value and provided prosperity for investors. The purpose of this study is to analyze the influence of profitability, investment decisions, and financing decisions on the value of mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. A total of 28 companies were selected as samples using purposive sampling techniques. The data analysis technique in this study uses Multiple Linear Regression Analysis processed using SPSS. Profitability has a negative and significant partial effect on Firm Value. Investment Decisions have a positive but insignificant partial effect on Firm Value. Financing Decisions have a negative and significant partial effect on Firm Value. The results of this study indicate that Profitability, Investment Decisions, and Financing Decisions have a positive and significant simultaneous effect on Firm Value.